2020
DOI: 10.3390/diagnostics10050263
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Methylating Mutations on Acute Myeloid Leukemia: Preliminary Analysis on 56 Patients

Abstract: Acute myeloid leukemia (AML) is a hematologic malignancy characterized by abnormal proliferation and a lack of differentiation of myeloid blasts. Considering the dismal prognosis this disease presents, several efforts have been made to better classify it and offer a tailored treatment to each subtype. This has been formally done by the World Health Organization (WHO) with the AML classification schemes from 2008 and 2016. Nonetheless, there are still mutations that are not currently included in the WHO AML cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…Moreover, the negatively correlated genes were observed to be linked to myeloid activation. This observation might add another argument to the importance of several genes like TET2/IDH1/2/WT1, NPM1 and RUNX1 in myeloid activation, as we and other groups have shown that the immature phenotype of AML is associated with TET2/IDH1/2/WT1 mutations [2,3]. This is also supported by the fact that RUNX1 has been shown to induce the expression of IL3 and SPI1, which are known for their importance in myeloid differentiation [15].…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Moreover, the negatively correlated genes were observed to be linked to myeloid activation. This observation might add another argument to the importance of several genes like TET2/IDH1/2/WT1, NPM1 and RUNX1 in myeloid activation, as we and other groups have shown that the immature phenotype of AML is associated with TET2/IDH1/2/WT1 mutations [2,3]. This is also supported by the fact that RUNX1 has been shown to induce the expression of IL3 and SPI1, which are known for their importance in myeloid differentiation [15].…”
Section: Discussionsupporting
confidence: 56%
“…Of the mutations that have been shown to be important in AML biology, of particular interest are mutations in TET2, IDH1, IDH2 and WT1, as they are known to influence both the epigenetic and transcriptomic landscape of AML [2]. These mutations are considered as having similar effects regarding the methylation changes, transcriptomic profile and immature phenotype they induce.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter compound (2-hydroxyglutarate) is sterically similar to α-ketoglutarate and acts as a competitive inhibitor to α-ketoglutarate-dependent enzymes [17]. Of those, an important α-ketoglutarate dependent enzyme is TET2, with IDH1/2 mutations being able to mimic the effect of TET2 mutations leading to a similar transcriptomic profile as we have previously shown [18].…”
Section: Classic Gene Mutations Mimicking Tet2 Lossmentioning
confidence: 66%
“…effect to that of TET2 mutation [39]. More than this, we have shown that mutations in WT1 are associated with similar methylation and transcriptomic profiles to that of TET2/IDH1/2 mutations in the case of AML [18]. In the same article, we proposed that TET2/IDH1/2/WT1 mutated AML to be considered as being similar to each other.…”
Section: Classic Gene Mutations Mimicking Tet2 Lossmentioning
confidence: 81%